2022
DOI: 10.1111/resp.14340
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function testing during SARS‐CoV‐2: An ANZSRS/TSANZ position statement

Abstract: The Thoracic Society of Australia and New Zealand (TSANZ) and the Australian and New Zealand Society of Respiratory Science (ANZSRS) commissioned a joint position paper on pulmonary function testing during coronavirus disease 2019 (COVID‐19) in July 2021. A working group was formed via an expression of interest to members of both organizations and commenced work in September 2021. A rapid review of the literature was undertaken, with a ‘best evidence synthesis’ approach taken to answer the research questions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…One such study, 21 which shares similarities with our research, demonstrates an inverse association between the SUA/SCr ratio and FVC and FEV1 in the general American population, although no association was observed with FEV1/FVC. Another study conducted in Japan, 13 involving 2917 participants, reported that the predicted values of FEV1% and FVC% in females were inversely associated with UA. A final study from Korea 22 was conducted, a retrospective cohort analysis comprising 19 237 individuals who underwent at least three health screenings and were followed up for over 5 years.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…One such study, 21 which shares similarities with our research, demonstrates an inverse association between the SUA/SCr ratio and FVC and FEV1 in the general American population, although no association was observed with FEV1/FVC. Another study conducted in Japan, 13 involving 2917 participants, reported that the predicted values of FEV1% and FVC% in females were inversely associated with UA. A final study from Korea 22 was conducted, a retrospective cohort analysis comprising 19 237 individuals who underwent at least three health screenings and were followed up for over 5 years.…”
Section: Discussionmentioning
confidence: 97%
“…One such study, 21 which shares similarities with our research, demonstrates an inverse association between the SUA/SCr ratio and FVC and FEV1 in the general American population, although no association was observed with FEV1/FVC. Another study conducted in Japan, 13 sue detriment and the impairment of alveoli and airways. [25][26][27][28][29] UA positively correlated with inflammatory markers, including TNFα, C-reactive protein, and IL-6.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…During the pandemic, the number of primary care spirometry tests in particular fell dramatically from prolonged disruptions that has now led to the deskilling of staff with probable loss of confidence in performing spirometry. This has only been partially reversed in the ‘living-with-COVID-19’ era78 due to ongoing concerns about the potential spread of SARS-CoV-2 virus to healthcare workers and patients through performing spirometry which can generate aerosol droplets, especially by inducing coughing 79 80…”
Section: Discussionmentioning
confidence: 99%